2012
DOI: 10.1186/1743-422x-9-13
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of EBNA-1 and LMP-1 variants in diseases associated with EBV infection in Chinese children

Abstract: BackgroundIn China, primary EBV infection occurs during childhood with seroprevalence reaching about 100% by 10 years of age. There are few studies on EBV variants in diseases associated with EBV infection in Chinese children. In this study, we investigated the diversity of the EBV genes (EBNA-1 and LMP-1) and the relationship between EBV variants and the clinical phenotypes in diseases associated with EBV infections in Chinese pediatric cases.ResultsThe frequencies of EBV type I in the IM, HLH and HL samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 37 publications
3
47
0
Order By: Relevance
“…On the other hand, co-infection with several EBV variants was reported in adult patients with IM [4648], probably given by a higher viral inoculum transmitted through kissing; however, in pediatric primary infection these co-infections are infrequent, as observed in our previous reports in other EBV genes [38,42,49] and by others [43,44]. Indeed, when studying chronic active EBV infection in children, Jin et al found a small proportion of co-infections but failed to do so in IM samples [44].…”
Section: Discussionmentioning
confidence: 68%
“…On the other hand, co-infection with several EBV variants was reported in adult patients with IM [4648], probably given by a higher viral inoculum transmitted through kissing; however, in pediatric primary infection these co-infections are infrequent, as observed in our previous reports in other EBV genes [38,42,49] and by others [43,44]. Indeed, when studying chronic active EBV infection in children, Jin et al found a small proportion of co-infections but failed to do so in IM samples [44].…”
Section: Discussionmentioning
confidence: 68%
“…The most frequent LMP1 variation is a 30 bp deletion (del‐LMP1) in the C‐terminus first detected in NPC patients from Southern China [Miller et al, ; Ai et al, ]. Nevertheless, several other authors have described the presence of this variation in other EBV‐associated malignancies while led to an increasing number of studies regarding the association with tumor development.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there are several hypotheses to explain the tumorigenicity of this variation [Mainou and Raab‐Traub, ]. The 30 bp deletion (168256–168287) results in the loss of 10 amino acid (codons 346–355), which are involved in the transformation effector site 2 (TES2) (codons 352–386), leading to a more oncogenic variant [Tao et al, ; Zhang et al, ; Chang et al, ; Ai et al, ]. In vitro, studies revealed that the del‐LMP1 has the capacity to transform established rodent fibroblasts and immortalize human keratinocytes, allowing cells to escape immunosurveillance [Li et al, ; Zhang et al, ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent report confirmed the subtypes but found no association with lymphoma (Habeshaw et al 1999). The variation might affect immune recognition of EBNA1 (Wrightham et al 1995;Chen et al 1999;Bell et al 2008) and has been noted in Chinese NPC samples (Ai et al 2012;Snudden et al 1995;Zhang et al 2004;Wang et al 2010a) and gastric cancer ), but there is no substantial evidence of disease association. It has been reported that the V-val subtype of EBNA1 has increased ability to activate the enhancer functions of oriP in transfection assays (Do et al 2008;Mai et al 2010).…”
Section: Ebnalmentioning
confidence: 95%